THE EFFECT OF FACE-TO-FACE LEARNING AND THE USE OF ZOOM MEDIA ON LEARNING OUTCOMES IN BULLET SHOT IN GRADE 8 A SMP MUHAMMADIYAH 3 BANYUWANGI - hakim, lukman (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
This research is a causal quantitative research which wants to know the application of face-to-face learning and the use of zoom media on the learning outcomes of shot put in Sports and Health Physical Education subjects. The respondents of this study were students of class 8A SMP Muhammadiyah 3 Banyuwangi school year with a total of 30 students. The research area was determined by purposive sampling method. This research is a quantitative research with a causal design. Data collection tools used questionnaires, tests, and documentation and interview methods. Degree valid and reliable with validity and reliability tests. Instrument analysis test using: 1) descriptive test, 2) normality test 3) homogeneity test. Hypothesis testing using: 1) regression analysis, 2) F test, 3) T test. The results showed that: 1) the sig. From the face-to-face learning variable there is a motivation of 0.000, so the conclusion is sig> 0.05, it means that there is an influence of face-to-face learning media on the interest in learning PJOK in students. 2) the sig value of the influence variable of learning media using zoom media on learning outcomes is 0,000. The conclusion that can be sig> 0.05, it means that there is an effect of learning media using zoom media on learning outcomes of PJOK in students. 3) the results of the regression analysis output obtained F count 29,124 with sig 0,000, because> 0.05, there is an effect of face-to-face learning media and the use of zoom media on learning outcomes of PJOK in students. Input for teachers needs to innovate and be creative in the learning process, especially in using technological advances in delivering mastery of student skill material, given that the abilities of each individual student are different with different means, educators must also be able to optimize technology for the purposes of improving the learning process so that learning outcomes are more maximum